2021
DOI: 10.1021/acs.jproteome.1c00373
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomics Integrating Novel Junction Peptide Identification Strategy Discovers Three Novel Protein Isoforms of Human NHSL1 and EEF1B2

Abstract: In eukaryotes, alternative pre-mRNA splicing allows a single gene to encode different protein isoforms that function in many biological processes, and they are used as biomarkers or therapeutic targets for diseases. Although protein isoforms in the human genome are well annotated, we speculate that some low-abundance protein isoforms may still be under-annotated because most genes have a primary coding product and alternative protein isoforms tend to be under-expressed. A peptide coencoded by a novel exon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This resulted in a total of 958,121 theoretical novel junction peptides with lengths ≥ 7 (excluding “X”) and masses < 3000, of which 535,766 had “X” at the N-terminus, while 422,355 had “X” at the C-terminus. The method of constructing a theoretical database of novel junction peptides has also been described in detail in our previous work …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This resulted in a total of 958,121 theoretical novel junction peptides with lengths ≥ 7 (excluding “X”) and masses < 3000, of which 535,766 had “X” at the N-terminus, while 422,355 had “X” at the C-terminus. The method of constructing a theoretical database of novel junction peptides has also been described in detail in our previous work …”
Section: Resultsmentioning
confidence: 99%
“…The method of constructing a theoretical database of novel junction peptides has also been described in detail in our previous work. 22 SpliceNovo first searches the MS/MS spectra against the theoretical novel junction peptide database and screens the top N (e.g., 20) novel junction peptides with unknown "X" at the N-terminus or C-terminus (Figure 1a). When calculating the match scores of incomplete novel junction peptides to the spectra, 21 types of fragment ions were considered (b, y, a, b(2+), y(2+), a(2+), b-H2O, y-H2O, a-H2O, b-NH3, y-NH3, a-NH3, and by-type internal ions between 2 and 10 in length).…”
Section: Analyticalmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluating the tools on human and mouse antibody data, the authors concluded that Casanovo and PointNovo show improved peptide recall across different enzymes and datasets compared with competing methods. Second, Tran et al [76] have evaluated PEAKS, PointNovo, Casanovo, and GraphNovo on five datasets: human tryptic data, Method Year Application Ind DeepNovo 2020 Detection of neoantigens [77] 2021 De novo sequencing in metaproteomics [78] ✓ 2021 Detection of neoantigens [79] ✓ 2021 Detection of junction peptides [80] ✓ 2021 Detection of shell proteins [81] ✓ 2023 Detection of neuropeptides [82] ✓ 2023 Detection of proteasome-generated spliced and non-spliced peptides [83] ✓ 2023 Antibody sequencing [84] ✓ 2023 Detection of short peptides [85] ✓ 2023 Noncanonical antigen detection [86] ✓ 2023 Detection of neoantigens [87] 2024 Antibody sequencing [88] ✓ 2024 Detection of neoantigens [89] 2024 Detection of venom proteins [ ✓ 2022 Detection of neoantigens [103] ✓ Table 3: Applications of deep learning de novo sequencing methods. The final column ("Ind") indicates whether the application was published independently of the original authors of the work.…”
Section: Performance Comparisonsmentioning
confidence: 99%